Recent advances in the application of metabolomics for food safety control and food quality analyses. Issue 9 (15th May 2021) - Li, Shubo; Tian, Yufeng; Jiang, Pingyingzi; Lin, Ying; Liu, Xiaoling; Yang, Hongshun
Abstract: As one of the omics fields, metabolomics has unique advantages in facilitating the understanding of physiological and pathological activities in biology, physiology, pathology, and food science. In this review, based on developments in analytical chemistry tools, cheminformatics, and bioinformatics methods, we highlight the current applications of metabolomics in food safety, food authenticity and quality, and food traceability. Additionally, the combined use of metabolomics with other omics techniques for "foodomics" is comprehensively described. Finally, the latest developments and advances, practical challenges and limitations, and requirements related to the application of metabolomics are critically discussed, providing new insight into the application of metabolomics in food analysis.